(untitled) (Huellas, 2019)
The provinces of Chaco and Formosa (Argentine Republic) have been shaped by the action of three mega alluvial cones, which are responsible for the topography, the runoff design and, consequently, the distribution of riverbank forests. The objective of this work is to apply Digital Elevation Models to generate runoff models which would determine the influence areas of the Gran Chaco mega alluvial cones in the distribution of jungles and forests in the Eastern Chaco within the Argentine territory. The results of the surface runoff models were compared with the forests and forests distribution in the Eastern Chaco, which had been obtained from Landsat images. By applying the Digital Elevation Models and their subsequent comparison with the distribution of forests, it was possible to determine the influence of the Otumpa hills in the regional geomorphology, and therefore the areas of influence of each mega alluvial cone and its influence on sediment deposition and forest distribution. It was determined that although mega alluvial cones are the main landscape shapers, the emergence of the Otumpa hills is mainly responsible for the depressed areas in the south of the region and the consequent distribution and density of jungles and forests.